INOVASI PELAYANAN PUBLIK KOTA INKLUSIF : KASUS PELAYANAN E-KTP DI KOTA PEKANBARU TAHUN 2021-2022 - Alya Rapidah; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The SIPINTAR PEDULI public service innovation is a new idea that was issued to assist people with disabilities in providing services in obtaining population or identity documents. The problem with this research is the inability of people with disabilities to attend the Population and Civil Registration Service to record and record e-KTP, therefore the Pekanbaru City Population and Civil Registration Service issued innovations that will make it easier for people with disabilities to get e-KTP. This study uses a qualitative approach research method and the type of research is descriptive. The research location was carried out at the Pekanbaru City Population and Civil Registration Office, using data collection techniques through interviews and documentation. The results of the study show that the innovation of the SIPINTAR PEDULI service carried out by the Department of Population and Civil Registration in 2021-2022 has progressed, this can be seen from the appreciation of the community and also assistance from local institutions that assist the Office of Population and Civil Registration in carrying out these innovations. The Department of Population and Civil Registration has demonstrated its existence in providing services, adequate facilities and infrastructure to support the service process. The service guarantee provided is so that all people with disabilities can have e-KTP and also the needs of people with disabilities can be met. Keywords: Innovation, e-KTP, People with Disabilities